2016
DOI: 10.7860/jcdr/2016/19171.8086
|View full text |Cite
|
Sign up to set email alerts
|

Actinomycotic Osteomyelitis of the Maxilla – A Delusive Presentation

Abstract: A 79-year-old female patient reported to the Department of Oral Medicine and Radiology, with a complaint of a progressively enlarging painless ulcer of the palate of six months duration. The ulcer caused difficulty in speech and swallowing due to nasal regurgitation. Her medical history revealed that she was a chronic diabetic patient with poor glycemic control. She was on insulin one year back and now on oral hypoglycemics. She gave a history of carcinoma breast and extensive esophageal candidiasis one year b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 4 publications
0
17
0
Order By: Relevance
“…While there are reports of actinomycotic osteomyelitis being successfully treated solely with antibiotics, 2 some investigators have reported healing with concurrent surgical treatment such as scraping of the granulation tissue and removal of cortical bone. 3,11 Sixteen (57.1%) of the 28 cases were managed with surgical measures, including curettage, cortical bone removal, and tooth extraction. In both our cases, surgical treatment and antibiotic administration were performed, and no relapse was observed over 2 years after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…While there are reports of actinomycotic osteomyelitis being successfully treated solely with antibiotics, 2 some investigators have reported healing with concurrent surgical treatment such as scraping of the granulation tissue and removal of cortical bone. 3,11 Sixteen (57.1%) of the 28 cases were managed with surgical measures, including curettage, cortical bone removal, and tooth extraction. In both our cases, surgical treatment and antibiotic administration were performed, and no relapse was observed over 2 years after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…1 Actinomycosis is a suppurative and granulomatous infection presenting in three clinical forms of cervicofacial, pulmonary and abdominopelvic. 7 Cervicofacial actinomycosis is more common in males between second to fifth decades of life and accounts for more than 60% of cases. It usually affects the mandible.…”
Section: Discussionmentioning
confidence: 99%
“…Infection progresses to form an abscess which breaks down, further leading to sinus tracts and fistulas extruding yellowish drainage containing sulfur granules. 7 These granules are small pale yellow lobulated flecks of 1-5 mm, composed of gram-positive, non-acid fast mycelia with hyphae growing out towards the periphery giving a radiating appearance which gives the organism its name. Clubs may be present at the periphery composed of antigen antibody complexes.…”
Section: Discussionmentioning
confidence: 99%
“…The exact pathophysiology of actinomycotic osteomyelitis is unclear; however it is suggested that inflammation begins when the normal composition of the microbial flora is disturbed (Meethal et al, 2016), resulting in serious infectious process that develops for over half of reported cases in the cervicofacial region. Of them only 0.5-9.0 % of the reports affect the maxillae (Esson & Lee, 2005).…”
Section: Discussionmentioning
confidence: 99%